Ring-Opening Polymerization of rac-Lactide by Bis(phenolate)amine-Supported Samarium Borohydride Complexes: An Experimental and DFT Study - Dyer, H; Huijser, S; Susperregui, N; Bonnet, F; Schwarz, A; Duchateau, R; Maron, L; Mountford, P (2010)
The synthesis and ring-opening polymerization (ROP) capability of bis(phenolate)amine-supported samarium borohydride and amide complexes are reported, together with a DFT study. Reaction of Na2O 2NL (L = OMe, NMe2, py, or Pr) with Sm(BH 4)3(THF)3 gave the borohydride complexes Sm(O2NL)(BH4)(THF) (L = OMe (2), NMe 2 (3), or py (4)) or Sm(O2NPr)(BH 4)(THF)2 (5). Compounds 4 and 5 lost THF in vacuo, forming phenolate O-bridged dimers 1 and 6, respectively. Reaction of H 2O2NL with Sm{N(SiHMe2) 2}3(THF)2 formed monomeric Sm(O 2NL){N(SiHMe2)2}(THF) (L = OMe (7), NMe2 (8), or py (9)) with tetradentate O2NL ligands, but dimeric Sm2(μ-O2NPr) 2(O2NPr)(THF) (10) with tridentate O 2NPr. Reaction of Sm{N(SiMe3)2} 3 with H2O2NL (L = OMe or NMe 2) led to zwitterionic products Sm(O2NL) (HO2NL). The bulkier amide compounds Sm(O 2NL){N(SiMe3)2}(OEt 2)n (n = 1, L = OMe (12) or py (13); n = 0, L = NMe 2 (14)) were prepared by reaction of Sm(O2N L)(BH4)(THF) with KN(SiMe3)2. The X-ray structures of 2, 5, 6, 7, 10, 13, and 14 were determined. The borohydrides 2-5 were very efficient initiators for the ROP of ε-CL, giving linear dihydroxytelechelic poly(ε-CL). Selected amide initiators were also assessed but gave poorer control, as judged by broad PDI (Mw/M n) values and significant amounts of cyclic poly(ε-CL)s. Of the borohydrides, only 2-4 were active for the ROP of rac-LA, and activity increased in the order O2NL = O2NOMe ≈ O2Npy < O2NNMe2. The latter ligand also gave the best control of the ROP, as judged by the PDIs and M n values. All gave heterotactically enriched poly(rac-LA) with P r values in the range 0.82-0.84. The ROP of rac-LA with the amides 7, 9, and 12 was faster but much less well controlled. Overall, the borohydride initiators were superior for the ROP of both ε-CL and rac-LA when compared to otherwise identical amide initiators. MALDI-ToF MS analysis of the poly(rac-LA) formed with 3 showed both-CH(Me)CHO and-CH(Me)CH2OH end groups originating from the insertion of the first LA monomer into the Sm-BH4 moiety of 3. In contrast, 2 and 4 formed only α,ω-dihydroxy-terminated polyesters with-CH(Me)CH2OH and-CH(Me)OH end groups. DFT calculations on Eu(O2′N NMe2)(BH4) found two mechanisms for the initial ring-opening step of LA by the borohydride group, giving pathways leading to either aldehyde-or alcohol-terminated poly(lactide)s. Of these two pathways, the one giving α,ω-dihydroxy-terminated polymers was the most favored, in agreement with experiment. (Ligand abbreviations: O2NL = RCH2N(CH2-2-O-3,5-C6H2tBu2)2 where R = CH2OMe, CH 2NMe2, py, or Et for L = OMe, NMe2, py, or Pr, respectively; O2′NNMe2 = Me2NCH 2CH2N(CH2-2-O-C6H4) 2.) © 2010 American Chemical Society.